The Intervention of Rural Enterprise Development Hub Project on Maize Production in Mqanduli: The Implication on Food Security Status of Maize Farmers - Sonwabo P. Mazinyo; Werner Nel; Enoch Terlumun Iortyom (Indonesian Journal of Geography, 2019)
The research analyzed the impact of the Rural Enterprise Development Hub Project (RED Hub Project) on food security of maize farmers. The data were analyzed using both inferential and descriptive statistics. Values were considered to be significant statistically where the P-value was less than 0.05. The study reveals a significant average increase in annual yield from 39.52 bags (50kg) to 87.02 bags (50kg) with a percentage increase of 120.19% per maize farm (t-statistics of 32.7 t-value and p-value of <0.05). Also, none of the maize farmers were food secure before the RED Hub project, 1 (0.5%) were mildly food insecure, 97 (48.5%) were averagely food insecure, and 102 (51%) were critically food insecure. After the RED Hub project intervention, 3.5% (7) are food secure, 104 (52%) are mildly food insecure, 76 (38%) are averagely food insecure and 13 (6.5%) critically food insecure. There was also more access and affordability of other food to meet maize farmers’ nutritional needs after the project intervention. An average of 72.5 (29.2%) beneficiaries and 99.3 (47.6%) beneficiaries respectively had access to other foods to meet their nutritional needs before and after the project intervention.